Tributyltin and Vascular Dysfunction: The Role of Oxidative Stress - Ronconi, Karoline de Sousa; Stefanon, Ivanita; Ribeiro Junior, Rogerio F. (Frontiers in Endocrinology, 2018)
The organotin compounds (OT) are used as fungicides, stabilizers in plastics, miticides, manufacturing and agricultural biocides, wood preservatives and antifouling agents. Tributyltin (TBT) is an OT that was first used for antifouling because it was the most effective agent to prevent undesirable accumulation of marine organisms on solid surfaces, such as ships' hulls or mechanical components, immersed in saltwater. TBT can be easily absorbed by mammals through ingestion, and its cytotoxic effects have become a major concern since their discovery in the 1970s. Recently, it has been demonstrated that TBT exposure is detrimental to the cardiovascular system. TBT is a membrane active substance and its action seems to depend on the OT lipophilicity. As a result, TBT crosses the cell membrane and damages the endothelium and the smooth muscle cells. TBT exposure induces vascular dysfunction, most likely due to endothelial dysfunction and morphological changes in the vascular wall. In an experimental rodent model, small doses of TBT (100 and 500 ng/kg/bw/day for 15 days) modified the vascular reactivity in aorta, mesenteric and coronary arteries followed by smooth muscle cell atrophy, increased collagen deposition and fibrin accumulation. TBT exposure increases oxidative stress by inducing vascular superoxide anion production derived from NADPH oxidase and decreases nitric oxide (NO) production as well as eNOS protein expression. The goal of this review is to summarize the current state of the art regarding the mechanisms involved in the vascular and endothelial dysfunction induced by TBT.